2006
DOI: 10.1161/01.hyp.0000232641.84521.92
|View full text |Cite
|
Sign up to set email alerts
|

Signal Switching, Crosstalk, and Arrestin Scaffolds

Abstract: H ormone agonists, including angiotensin II (Ang II), norepinephrine, urotensin II, endothelin-1, vasopressin, and serotonin, mediate a plethora of physiological and pathological cardiovascular events via their cognate 7 membrane-spanning G protein-coupled receptors (GPCRs). On ligand binding, GPCRs undergo conformational changes that enable the activation and dissociation of heterotrimeric guanine nucleotide binding proteins (G proteins) and trigger a range of intracellular second messenger signaling cascades… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 80 publications
0
20
0
Order By: Relevance
“…As a result of this switch in G-protein usage, downstream signaling transitions from cAMP/PKA pathways to MAPK activation. G-protein switching has been noted for the ␤2-adrenergic receptor both in vitro and in vivo and has been suggested to contribute to the development of cardiac hypertrophy in states of chronic catecholamine excess (61,62). Recent data have also demonstrated that association of the ␤2-adrenergic receptor with ␤-arrestin can modulate the magnitude of G-protein switching (63).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result of this switch in G-protein usage, downstream signaling transitions from cAMP/PKA pathways to MAPK activation. G-protein switching has been noted for the ␤2-adrenergic receptor both in vitro and in vivo and has been suggested to contribute to the development of cardiac hypertrophy in states of chronic catecholamine excess (61,62). Recent data have also demonstrated that association of the ␤2-adrenergic receptor with ␤-arrestin can modulate the magnitude of G-protein switching (63).…”
Section: Discussionmentioning
confidence: 99%
“…Dynamic feedback switching from G␣ s to G␣ i usage has been documented to occur in response to ligand binding for several receptors, including the ␤1-and ␤2-adrenergic receptors, the prostacyclin receptor, and the vasoactive intestinal polypeptide receptor (45,(57)(58)(59). This particular phenomenon of G-protein switching has been most intensively studied for the ␤2-adrenergic receptor (57,60,61). Binding of ligand to this receptor leads to activation of G␣ s , generation of cAMP, and PKA-mediated phosphorylation of sites within the third intracellular loop and C-terminal tail of the receptor (57).…”
Section: Discussionmentioning
confidence: 99%
“…While the highest proportion of ␤-ARs in the heart are ␤ 1 -receptors, the proportion of ␤ 2 -receptors increases with heart failure, as ␤ 1 -ARs are downregulated during chronic stimulation (754,828,1010). Adenoviral gene transfer of two different naturally occurring ␤ 1 -AR polymorphisms to isolated rodent cardiac myocytes had significant chronotropic effects, and one of the ␤ 1 -AR variants greatly enhanced the sensitivity of the myocytes to a common ␤-blocker used to treat heart failure (751).…”
Section: ␤-Adrenergic Receptors and G Proteinsmentioning
confidence: 99%
“…␤ 2 -ARs signal via multiple downstream pathways. Gene transfer of ␤ 1 -AR or ␤ 2 -AR into double knockout mice indicated that the protective effects of ␤ 2 -AR are likely mediated via G␣ i and the downstream activation of phosphoinositide 3-kinase (PI3K) and Akt (477,1015) or via functionally discrete signaling pools (506,828).…”
Section: ␤-Adrenergic Receptors and G Proteinsmentioning
confidence: 99%
“…In case of AT1r, the transactivation of EGFR and stimulation of MAPK is brought about by a variety of mediators [55,59], independently of a specific agonist. The same is true of AT2r and the production of nitric oxide, the essential end mediator of its effects, does not always require the selective agonist angiotensin II [60].…”
Section: Angiotensin Receptorsmentioning
confidence: 99%